2019
DOI: 10.1016/j.fsigen.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Forensic tri-allelic SNP genotyping using nanopore sequencing

Abstract: The potential and current state-of-the-art of forensic SNP genotyping using nanopore sequencing was investigated with a panel of 16 tri-allelic single nucleotide polymorphisms (SNPs), multiplexing five samples per sequencing run. The sample set consisted of three single-source human genomic reference control DNA samples and two GEDNAP samples, simulating casework samples. The primers for the multiplex SNP-loci PCR were taken from a study which researched their value in a forensic setting using conventional sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The performance of the software used for base calling and further downstream analyses is also crucial, and is the subject of continuous improvements. The platform already evolved in such a way that the MinION sequencer is now capable of correctly genotyping forensic SNP loci [14,15]. The first attempts to assess nanopore sequencing for STR-profiling have been reported recently [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the software used for base calling and further downstream analyses is also crucial, and is the subject of continuous improvements. The platform already evolved in such a way that the MinION sequencer is now capable of correctly genotyping forensic SNP loci [14,15]. The first attempts to assess nanopore sequencing for STR-profiling have been reported recently [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of long MinION reads represented self-chimeras that were not recognized by the chimera filtering software. This issue was common on PacBio RSII instrument (Tedersoo et al,77 2018), but it was not observed in the current Sequel runs. Since MinION reads are typically mapped to reference, 78…”
Section: Discussion 54mentioning
confidence: 84%
“… As the MinION flow cells possessed suboptimal number of active pores, the sequencing time might be overestimated. Nanopore sequencing accuracy might be improved with ‘1D 2 ′ chemistry, at the expense of lower sequencing depth [ 30 ]. Nanopolish could not improve the detection of minor variants, which might be caused by high error rate of Nanopore raw data.…”
Section: Discussionmentioning
confidence: 99%